The effects of health care programs for gestational diabetes mellitus in South Korea: a systematic review - Seo Jin Park; Jina Lee (Korean Society of Women Health Nursing, 2020)
Purpose The purpose of this study was to investigate the effects and characteristics of health care programs for pregnant women with gestational diabetes mellitus (GDM) in Korea. Methods This study was conducted according to the Cochrane Collaboration's systematic literature review handbook and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses reporting guideline. We searched eight international and domestic electronic databases for relevant studies. Two reviewers independently selected the studies and extracted data. For each study, information on the research method, participants, characteristics of the program, and results were extracted using a previously established coding table. The National Evidence-based Healthcare Collaborating Agency's risk of bias assessment tool for non-randomized studies was used to assess the risk of bias of the included articles. A qualitative review of the selected studies was performed because the interventions differed considerably and the measured outcomes varied. Results Out of 128 initially identified papers, seven were included in the final analysis. The risk of bias was evaluated as generally low. Health care programs for pregnant women with GDM showed positive effects on blood glucose control. Anxiety and depression were reduced, and self-management and self-care behavior, self-efficacy, and maternal identity improved. Conclusion Our study provides clinical evidence for the effectiveness of health care programs for pregnant women with GDM, and its results can be used to support the development of health care programs for GDM. More well-designed research is needed on GDM, especially studies that deal with emotional stress and apply a family-oriented approach.